Packed activated carbon particles triggered a more robust syntrophic pathway for acetate oxidation-hydrogenotrophic methanogenesis at extremely high ammonia concentrations. (May 2022) - Zhou, Man; Li, Cheng; Ni, Fuquan; Chen, Anjun; Li, Meiliang; Shen, Guanghui; Deng, Yu; Deng, Liangwei
Abstract: To date, the anaerobic digestion (AD) of chicken manure has been difficult because of the inhibition caused by high ammonia nitrogen levels. In this study, granular activated carbon (GAC), zeolite, and medical stone (MS) were added to improve dry AD of chicken manure. The semi-continuous processes amended with GAC were stable throughout the experiment despite the presence of extremely high NH4 + -N (∼11 500 mg L −1 ) and NH3 –N (∼2350 mg L −1 ) levels. By adding GAC, the methane yield increased from 0.115 L g −1  VS in phase I to 0.128 L g −1  VS in phase III. The methane yield of zeolite group, MS group and control group decreased from ∼0.041 to 0.098 L g −1  VS in phase I to ∼0.005–0.012 L g −1  VS in phase III. The addition of zeolite improved dry AD during the early stage, but there was no improvement when MS was added. Different hydrolysis efficiency of macromolecular compounds and GAC adsorption of ammonium contributed to the improved biogas production, but the key reason for the improvement was promotion of the syntrophic acetate oxidation-hydrogenotrophic methanogenesis pathway. In contrast to previous studies, the GAC was not lost along with the digestate discharge because the activated carbon was packed in nylon bags with holes. Graphical abstract: Image 1